KONSEP UMAT DALAM AL-QUR’AN: MENGGALI NILAI-NILAI APRIORI DAN APOSTERIORI SOSIAL - Ammar Fauzi (Sekolah Tinggi Agama Islam (STAI) Sadra, 2015)
Although the word ‘umat’has been standarized in the Indonesian vocabulary and could be easily found in the Qur’an, it seems that this term has not been commonly and uniquely emerging in the sociology and politics literatures in Bahasa Indonesia. So far, in common sense and lexical meaning, the term of ‘umat’ ordinarily connotes a kind of religious belief. However, how the concept of ‘umat’ should be described in the view of the Quran? It is evident that to incarnate the real unity and integrity is utopia amid various world views, but the islamic faith and thought could be an element that capture the diversity and differences of Muslim people into a core, i.e. the one umat (community) in its typical and complete sense encompassing a priori and a posteriori values.